PENGARUH GAYA KEPEMIMPINAN DALAM RANGKA MENINGKATKAN KINERJA GURU PADA SMA MALAHAYATI JAKARTA TIMUR - Uniki, Husniadi (JURNAL KEBANGSAAN, 2019)
ABSTRACT Leadership is one of the factors that shape and help others to work and enthusiastic achieve planned objectives. In relation to the success of an organization realize its goal, most determined by leadership style and the high performance of subordinates in carrying out his duties. This study aimed to analyze the influence of leadership styles in order to improve the performance of teachers at Senior High School Malahayati East Jakarta. Research conducted in Cijantung, Pasar Rebo, East Jakarta, taking the number of respondents as the sample by 40 respondents are teachers who teach at senior high school Malahayati Jakarta to share research questionnaire. The method of analysis used in this study is a simple linear regression analysis where the analysis can be used to look at the relationship and influence of leadership style on the teachers performance of senior high school Malahayati East Jakarta. Based on the analysis and calculation of the results of research on the model of the relationship between leadership style and teacher performance found a positive relationship, it can be seen from the results of simple regression calculation. The regresi linier model is Y = 23.995 + 0.533 X. Results from the study also showed that 33.7% teachers performance at senior high school Malahayati Jakarta can be explained by leadership style factors. While the remaining 66.3% is explained by other reasons. Another factor to be taken to ensure that teacher performance can increase even more, such as a comfortable working environment and conducive adequate working facilities, provision of benefits, rewards, and promotions. Keyword: leadership, performance of teachers